The Interactions of Rhizodeposits with Plant Growth-Promoting Rhizobacteria in the Rhizosphere: A Review - Hassan, Mohammad; McInroy, John; Kloepper, Joseph (Agriculture (Basel), 2019)
Rhizodeposits, root exudates, and root border cells are vital components of the rhizosphere that significantly affect root colonization capacity and multiplication of rhizosphere microbes, as well as secretion of organic bioactive compounds. The rhizosphere is an ecological niche, in which beneficial bacteria compete with other microbiota for organic carbon compounds and interact with plants through root colonization activity to the soil. Some of these root-colonizing beneficial rhizobacteria also colonize endophytically and multiply inside plant roots. In the rhizosphere, these components contribute to complex physiological processes, including cell growth, cell differentiation, and suppression of plant pathogenic microbes. Understanding how rhizodeposits, root exudates, and root border cells interact in the rhizosphere in the presence of rhizobacterial populations is necessary to decipher their synergistic role for the improvement of plant health. This review highlights the diversity of plant growth-promoting rhizobacteria (PGPR) genera, their functions, and the interactions with rhizodeposits in the rhizosphere.